ATTITUDE TOWARD COMPENSATION AND EMPLOYEE ENGAGEMENT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Mora, Linda; Rahman Hakim, Arif; Agustriyana, Darwis (International Journal of Psychosocial Rehabilitation, 2020)
Attitude toward compensation is the response of a person (employee) to the compensation given by the company for what the employee has given or done for the company. The better the compensation given to employees can increase job satisfaction and employee attachment to the organization, can help attract potential employees to join the company and maintain and retain productive employees. This study aims to determine the influence of attitudes on compensation and employee engagement on Organizational Citizenship Behavior (OCB). This type of quantitative research, with a population and sample that is all employees taff position in mining contracting companies, amounting to 50 employees. The sampling technique in this study used a census with data collection methods using a measuring instrument in the form of a questionnaire with a Likert scale type. Validity in this study uses content validity, with the validity of the ratio of this study using the method of content validity ratio (CVR). Testing the analysis of measuring instrument items was calculated by Pearson's product moment correlation equation and reliability testing by Cronbach's Alpha technique. Data analysis method with multiple analysis techniques. Based on the results of the regression test above, the value obtained by sig. 0.00